Implementation of the Think Pair Share (TPS) Cooperative Learning Model to Improve Chemistry Learning Outcomes for Class X TKJ 1 SMKN 2 Palembang Students - Mia Wulansari; Muhammad Hadeli L; Rahma Aini (Institute of Multidisciplinary Research and Community Service, 2022)
Abstract: Classroom action research using Think Phair Share (TPS) learning model in class X TKJ 1 SMKN 2 Palembang aims to improve students' learning outcomes and interest in learning chemistry. The study was conducted in two cycles, each cycle consisting of two meetings. The data were obtained by using observation sheet, questionnaire and test instrument of student learning result which was done at the end of the meeting. Improvement of student learning outcomes can be seen from the average of student learning outcomes before the action done (T0) of 70,6 with mastery learning 40%, an increase in cycle I (T1) to 80,5 with mastery learning 77,1% and in cycle II (T2) increased to 88,9 with learning mastery 88,6%. And students’ interest in learning increased from 42,7%before the application of the TPS learning model to 79,6% after the determination of the TPS model in Cycle I (T1). While in in Cycle II (T2) students’ interest in learning increased from 52,1% before the application of the TPS learning model to 89,15% after the determination of the TPS model .Keywords: classroom action research, think phair share model, student chemistry learning result, interest learnin